AN EXPERIMENTAL CALIBRATION OF THE TEMPERATURE DEPENDENCE OF OXYGEN ISOTOPE FRACTIONATION BETWEEN APATITE AND CALCITE AT HIGH TEMPERATURES (350-800°C) - Fortier S.M.; Luttge A. (My University, 1995)
The fractionation of oxygen isotopes between apatite and calcite has been measured experimentally using the direct exchange technique in a piston-cylinder apparatus at high temperature and pressure (350-800°C, 1.1 GPa). The fractional approach to equilibrium ranged from 20% to 80% and varies systematically with temperature and run duration. Isotopic, XRD and SEM analyses of the run products indicate that the exchange occurs dominantly by recrystallization in the early stages of the experiments. The equilibrium fractionation over the temperature range of this study ranges from # -5.5 to # -2%% but the data at 350° and 425°C have relatively large errors. For T=<500°C an error-weighted least-squares fit yields: 1000 ln αap - cc = -0.68 - (1.60 +/- 0.26) . 106 T-2The magnitude of the temperature dependence is intermediate to that for felsic and mafic minerals relative to calcite. Mineral pairs involving apatite are potentially useful indicators of temperature, cooling rates and equilibrium/disequilibrium phenomena in igneous and metamorphic rocks.